The use of education robotics as a teaching tool for physics: Newton’s Laws - Lima, João P. R. de; S. Filho, Paulo C. Da; Rossiter, Sarah T. de S.; Albino, Maria Da G. F. Do N. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
This article presents Educational Robotics as a tool for teaching physics. In this perspective, a study was conducted to identify the potential benefits of using Educational Robotics to teach Newton’s Laws. The data collection method employed was observation, which was carried out according to a pre-determined observation plan designed to assess student engagement during class activities. The results obtained demonstrated that the integration of Educational Robotics can serve as an alternative approach to motivate the learning of physics concepts. It makes the subject more engaging, appealing, and, to some extent, helps to overcome biases that may arise from a non-scientific society or traditional teaching methods.